2017
DOI: 10.4103/ortho.ijortho_260_17
|View full text |Cite
|
Sign up to set email alerts
|

Role of High Tibial Osteotomy in Cartilage Regeneration – Is Correction of Malalignment Mandatory for Success?

Abstract: Malalignment of the knee can cause debilitating symptoms such as pain, resulting in a decline in function and mobility. Surgical options that exist to address this problem include realignment osteotomies and joint replacements. Realignment osteotomies are the more appropriate options in certain patient populations, especially with regard to age and level of activity. Since a high tibial osteotomy (HTO) was first used to manage malalignment of the knee and osteoarthritis, different techniques involving the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 55 publications
0
13
1
3
Order By: Relevance
“…The results for HTO patients contradict those found in literature, in which quantitative cartilage restoration was seen, although most studies used second-look arthroscopy to visually score cartilage restoration after HTO, and discrepancies may be expected between such different scoring/measurement methods [ 38 ]. Two studies have suggested that cartilage gain occurs after HTO using the same MRI measurement method as used in the current study, although in both cases the increases were not statistically significant [ 39 , 40 ].…”
Section: Discussioncontrasting
confidence: 60%
“…The results for HTO patients contradict those found in literature, in which quantitative cartilage restoration was seen, although most studies used second-look arthroscopy to visually score cartilage restoration after HTO, and discrepancies may be expected between such different scoring/measurement methods [ 38 ]. Two studies have suggested that cartilage gain occurs after HTO using the same MRI measurement method as used in the current study, although in both cases the increases were not statistically significant [ 39 , 40 ].…”
Section: Discussioncontrasting
confidence: 60%
“…[17] Osteotomi ile birlikte mozaikplasti uygulamasının özellikle ikinci bakış artroskopisi ile değerlendirilmesi literatürde çok yer bulmamıştır ve bu kombine işlemin objektif etkilerinin değerlendirilebilmesi için yeni çalışmalara gereksinim olduğu gözlenmektedir. [5] Otolog kondrosit implantasyonu defekt alanının cm 2 'nin altında olduğu, 30 yaşından genç hastalarda ve dizilim düzeltici osteotomi ile birlikte uygulandığında daha iyi sonuç vermektedir. [28] Kim ve ark.…”
Section: Osteotomi̇ İle Bi̇rli̇kte Mozai̇kplasti̇ Uygulamasiunclassified
“…[4] Özellikle genç, aktif, eklem hareket açıklığı geniş, bağ laksitesi olmayan izole medial osteoartritli hastalarda medial açık kama osteotomisi iyi sonuç veren ve komplikasyonu daha az bir cerrahi yöntemdir. [4][5][6] Tek kompartman artrozu olan hastalarda dizilimi düzelten osteotomi tek başına yapılabileceği gibi, abrazyon, subkondral drilleme veya mikrokırık, otolog kondrosit implantasyonu, mozaikplasti, trombositten zengin plazma ve kök hücre tedavileri gibi kıkırdak restorasyonunu amaçlayan işlemler birlikte de yapılabilir. Diğer taraftan bakıldığında da, kıkırdak yenileyici bir işlem yapılması planlanan hastalarda eğer dizilim bozukluğu varsa düzeltici osteotomi de eklenmelidir.…”
unclassified
“…The use of MSCs for regeneration of the musculoskeletal system is an area of much basic science research and evolving clinical applications[ 51 - 54 ]. Over the past twenty years, MSCs have been used clinically in a variety of scenarios to enhance the outcome for orthopedic patients from the standpoint of both wound healing and pain[ 55 ]. Dating back to the 1980s, bone grafting and bone marrow injection into fracture sites has been utilized to enhance union[ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fifty-three of the 60 patients went on to union at an average of twelve week[ 56 ]. Clinical applications of MSCs have since expanded to include healing of high-tibial osteotomies, large bone defects after total hip arthroplasty and trauma, distraction osteogenesis, treatment of avascular necrosis, articular cartilage defects, tendinopathy (patellar, lateral epicondylitis), spinal fusion, and treatment of bone cysts[ 2 , 4 , 31 , 55 , 57 - 60 ]. These findings paved the way for future use and investigations to understand the mechanisms underlying the observed wound healing effects.…”
Section: Introductionmentioning
confidence: 99%